The Administrative Model for the Staff’s Competency Development of Division Student Development in Higher Education Institutes to Develop College Students in the 21st Century - Chumphon, Prasat; Meekun , Kosol; Poovatanakul , Vipaporn; Rasanond, Tharin (Journal of Buddhist Education and Research (JBER), 2024)
This research aimed to 1) identify the key causal factors influencing the competencies of student development staff in higher education institutions, 2) examine the competency development models for these staff members, and 3) design and evaluate the practical applicability of an administrative model for competency development. A mixed-methods approach combining quantitative and qualitative research was employed, involving 280 student development staff members selected using stratified random sampling. The research instruments included 11 standardized assessment tools with reliability (α = .900 to .916) and an evaluation form for the administrative model. Statistical analyses comprised descriptive and inferential statistics, including t-tests, one-way ANOVA, multiple regression, and path analysis. The findings revealed that key causal factors influencing staff competencies included external factors such as (1) support from close associates, (2) the university environment, (3) governance by administrators, and (4) university culture, as well as internal factors like self-efficacy in student development work, collectively explaining 58.5% of the variance in staff competencies. The proposed competency development model was empirically validated, explaining 98.3% of the variance (R2 × 100), while the administrative model was rated by experts with average scores exceeding 92%, surpassing the evaluation threshold of 70/75.